Motivation and Job Commitment in the Higher Education Sector: A Case Study of Nigerian Colleges of Education - Khadijatu Adamu Mafindi (Walidem Institute and Publishing, 2024)
This study explores the relationship between motivation and job commitment among academic staff in Nigerian Colleges of Education, emphasizing both financial and non-financial motivational factors. Motivation significantly impacts the behaviour and performance of academic staff, affecting their engagement in teaching, research, and community service. Utilizing a correlational research design, this study examines personnel management practices such as recruitment, training, development, and discipline and their effects on job commitment. The findings reveal that financial incentives, such as salaries and overtime compensation, and non-financial motivators, like professional recognition and working conditions, play crucial roles in fostering job commitment. The study employs a correlational research design to examine the relationship between personnel management practices, such as recruitment, training, development, motivation, and discipline—and academic staff job commitment However, gaps exist in providing adequate non-financial benefits like accommodation and health services. The study concludes with recommendations for enhancing both financial and non-financial incentives and improving work environments to boost job commitment among academic staff in Nigerian Colleges of Education.